Pengaruh ROA, NIM, dan EPS terhadap Harga Saham Perusahaan Perbankan - Tiara Oktapia Maharany; Riyandi Nur Sumawijaja (Forum Kerjasama Pendidikan Tinggi, 2026)
This study investigates the influence of Return on Assets (ROA), Net Interest Margin (NIM), and Earnings per Share (EPS) on the stock prices of state-owned banks listed on the Indonesia Stock Exchange. A quantitative research design was adopted using descriptive and verificative approaches. The study population consisted of all state-owned banks listed on the Indonesia Stock Exchange throughout the 2015–2025 period. Sample selection was conducted using purposive sampling, resulting in four state-owned banks with a total of 44 observations. The data were processed and analyzed using IBM SPSS Statistics. The empirical findings reveal that the regression model explains 40.4% of the variation in stock prices, as indicated by the coefficient of determination (R²), while the remaining 59.6% is attributable to variables beyond the scope of the proposed model. The partial regression results demonstrate that ROA and EPS exert a positive and statistically significant effect on stock prices, whereas NIM does not exhibit a statistically significant relationship. Furthermore, the simultaneous test confirms that ROA, NIM, and EPS collectively have a significant effect on the stock prices of state-owned banks listed on the Indonesia Stock Exchange. These findings indicate that profitability indicators, particularly ROA and EPS, are more strongly associated with stock price movements than NIM during the observation period.